Pengaruh Infus Herba Meniran (Phyllanthus niruri L) Terhadap Daya Larut Kalsium Batu Kandung Kemih - Widodo, Agustinus (Media Eksakta, 2011)
The aim of this research is to determine the most effective concentration of â€œmeniranâ€ herb infuse in drawnâ€“out the calcium of bladder stone.Â  The concentration of infuse was varied in 2 %, 6 %, 10 %, 14 % and 18 % w/v, then they were added with 100 mg of the bladder stone.Â  The calcium analysis was done by Atomic Absorption Spectrophotometer and this study was formatted in the Completely Randomized Design.Â  The F test indicate that â€œmeniranâ€ herb infuse increase the calcium solubility of bladder stone significantly and the Duncanâ€™s multiple range test also show that the most effective concentration is 10 % w/v.